A meta-analysis: Internet mindfulness-based interventions for stress management in the general population. Issue 28 (10th July 2020) - Zhang, Yun; Xue, Jiaming; Huang, Ying
Abstract: Background: Psychological stress was an important mental health problem among the general population and warrant research to inform strategies for effective prevention. iMBIs provide a possibility to offer easily accessible, efficacious, convenient, and low-cost interventions on a wide scale. However, the efficacy of iMBIs in the general population remains unclear. The aim of this meta-analysis is to evaluate the effects of iMBIs for stress reduction in the general population. Methods: A systematic search in PubMed, Embase, Web of Science, Medline, Cochrane Library, CNKI, and Wanfang Data databases was performed up to April 10, 2019. The overall effect sizes of the iMBIs on stress, depression, anxiety, and mindfulness were recorded by the metric of Hedges' g with 95% confidence interval (CI), Z-value, and P value. Results: Sixteen eligible studies were included in the meta-analysis. The overall results indicated that iMBIs had small to moderate effects on stress (Hedges' g  = −0.393) and mindfulness (Hedges' g  = −0.316) compared with the control group. Results from subgroup analyses revealed that the type of sample and delivery mode had a greater impact on heterogeneity across the studies. Meta-regression found that the overall effect might be moderated by guidance for iMBIs. Conclusion: The present meta-analysis suggested that iMBIs had small to moderate effects in reducing stress and improving mindfulness of the general population in comparison with the control group. Future research is needed to explore how iMBIs are remolded to improve adherence and suit specific individuals.